2022
DOI: 10.21931/rb/2022.07.02.46
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of urinary tract infections in patients with resistance genes towards antibiotics

Abstract: Escherichia coli are gram-negative bacteria that cause urinary tract infections (UTIs). UTIs have affected a significant percentage of humans yearly due to bacterial infection. Our study aims to determine the prevalence of resistance genes in E. coli towards sulfamethoxazole. This study included (490) patients with UTIs, and the urine samples were cultured on media. The patients were admitted to the Medical City in Baghdad to treat UTIs. 116 E.coli isolates were isolated from urine specimens, 35 isolates of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The results observed that all the isolates of Klebsiella pneumoniae, E. coli, proteus mirabilis, Burkholderia cepacia and Klebsiella oxytoca ) were negative for the presence of bla CTX-M1, bla CTX-M2, and bla CTX-M9 genes. Molecular detection of CTX -M ESBLs for isolate Pseudomonas aeruginosa showed that 1 (8.3%) of the isolate was positive for at least one CTX-M ESBLs gene from 12(60%) , the frequency of CTX-M ESBLs gene presence among Pseudomonas aeruginosa was as follows: blaCTX-M1 ,1(8.3%); bla CTX-M2, 1(8.3%); bla CTX-M9 0(0%) ,there was a significant association between the presence of ESBL genes in Pseudomonas aeruginosa and site of infection ,our study consistent with this study with in Jimma, Ethiopia [33,34] containing this bla CTX-M2 in the (3%); (8.2%) respectively. The results was consistent with [35] demonstrated the frequencies of this gene blaCTX-M1 (10%) in Erbil.…”
Section: Molecular Detecting Antibiotic Resistance Genes In Gram Nega...supporting
confidence: 89%
“…The results observed that all the isolates of Klebsiella pneumoniae, E. coli, proteus mirabilis, Burkholderia cepacia and Klebsiella oxytoca ) were negative for the presence of bla CTX-M1, bla CTX-M2, and bla CTX-M9 genes. Molecular detection of CTX -M ESBLs for isolate Pseudomonas aeruginosa showed that 1 (8.3%) of the isolate was positive for at least one CTX-M ESBLs gene from 12(60%) , the frequency of CTX-M ESBLs gene presence among Pseudomonas aeruginosa was as follows: blaCTX-M1 ,1(8.3%); bla CTX-M2, 1(8.3%); bla CTX-M9 0(0%) ,there was a significant association between the presence of ESBL genes in Pseudomonas aeruginosa and site of infection ,our study consistent with this study with in Jimma, Ethiopia [33,34] containing this bla CTX-M2 in the (3%); (8.2%) respectively. The results was consistent with [35] demonstrated the frequencies of this gene blaCTX-M1 (10%) in Erbil.…”
Section: Molecular Detecting Antibiotic Resistance Genes In Gram Nega...supporting
confidence: 89%
“…So antibiotics have difficulty linking to the target. Meanwhile, trimethoprim resistance in E. coli is caused by chromosomal mutations in the dhfr or dhps genes, which cause antibiotic resistance 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 68 isolates were positive for int1 from integron genes (28). In the study conducted to determine the sulphonamide resistance genes in E. coli isolates that cause UTI in Uruguayan children, resistance to trimethoprim/sulfamethoxazole was detected in 37.9% of the samples, and it was stated that sul resistance gene was found in 85.5% of them (29).…”
Section: Discussionmentioning
confidence: 99%